Chemical Characteristics Comparison of Palm Civet Coffee (Kopi Luwak) and Arabica Coffee Beans - Ifmalinda Ifmalinda; Imas Siti Setiasih; Mimin Muhaemin; Sarifah Nurjanah (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
Chemical characteristics of coffee are depended on types of coffee. Different types of coffee have the unique characteristic. Chemical components have significant effects on taste and aroma of brewing. Those characteristics are the result of volatile and nonvolatile components during roasting then affecting taste. Kopi Luwak has distinct chemical and taste from regular coffee. On previous research, Marcone (2004b) and Mahendratta et al. (2011) explained that quality improvement on Kopi Luwak is result of lower protein content and higher fat content compared to regular coffee. Lower protein content reduces bitter taste while higher fat content can increase body or feeling heavy. The aim of this research was to obtain information about chemical compound of Kopi Luwak and regular Arabica coffee. From this study, it can be analyzed that protein content of regular green coffee beans was 9.48%, and regular roasted bean was 11.3% while protein content of Kopi Luwak green bean was 8.8%, and its roasted bean was 10.12%. Further, caffeine content had been analyzed where regular coffee beans contained 0.70% and its roasted bean contained 0.61% while caffeine content of green bean from Kopi Luwak was 0.51%, and its roasted bean was 0.47%. pH valued was also observed where regular green bean was 6.7 and regular roasted bean was 6.9 while green bean of Kopi Luwak was 5.3 and its roasted bean 5.7. Moreover, sugar content of regular coffee beans was 1.9% and its roasted bean was 0.015% while sugar content of Kopi Luwak green bean was 1.6% while its roasted bean was 0.013%. Fat content of regular green coffee beans was 8.5% and its roasted bean was 11.7% while fat content of Kopi Luwak green bean was 9.3% and its roasted bean was 12.2%. Fatty acid content of regular coffee beans consisted of hexadecanoic acid with area 40.3%, Kopi Luwak bean was 44.3%, and octadecenoic content with area 2.46% while Kopi Luwak bean was 7.12%.